The potential of standardized quassinoid-rich extract of Eurycoma longifolia in the regulation of the oestrous cycle of rats - Abdul Rahman, Suzanah; Ahmad, Nur Amalina; Abdul Samat, Nadia Hanis; Zahri, Syazana; Abdullah, 'Afif Raihan; Chan, Kit-Lam (2017)
Objective: To evaluate the effects of Eurycoma longifolia (E. longifolia) standardized extract on the oestrous cycle, levels of reproductive hormones and histology of the ovaries of Sprague-Dawley rats. Methods: Female rats were orally treated with E. longifolia standardized extract at the dose levels of 2.5, 5.0, 10.0, 25.0, 50.0 and 100.0 mg/kg of body weight over 5 days. Vaginal smears were monitored daily within the duration and after withdrawal of the treatment before being sacrificed. The body weights of the females were recorded before and after the 5 days treatment. At the end of the experiments, blood samples were collected for determination of testosterone, oestradiol and progesterone levels. Ovaries were removed, weighed and examined for histomorphological changes. Results: The administration of E. longifolia standardized extract did not significantly alter the oestrous cycle of the rats during the 5 days treatment and after withdrawal of the treatments. This was supported by normal testosterone, oestradiol and progesterone levels as well as normal morphology of the ovaries. Conclusions: The data obtained showed that E. longifolia standardized extract did not exhibit any toxic effect on reproductive activities of female rats suggesting potential use in the management of infertility.